2009
DOI: 10.3177/jnsv.55.506
|View full text |Cite
|
Sign up to set email alerts
|

The Different Effects of Fluid with and without Carbohydrate Ingestion on Subjective Responses of Untrained Men during Prolonged Exercise in a Hot Environment

Abstract: SummaryThis study examined the effects of maintaining euhydration by ingesting fluids with or without carbohydrate on subjective responses of untrained men during prolonged exercise in a hot environment. Six healthy untrained subjects completed 90 min of cycling exercises at 55% maximal oxygen consumption (V O 2 max ) in a hot environment (temperature: 28˚C, humidity: 50%) under three different experimental conditions. During the first trial, subjects did not ingest fluids during exercise (dehydration (DH) tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
2
8
1
Order By: Relevance
“…Similar results have been reported in other studies investigating the effects of progressive dehydration on RPE (16,20). It is speculated that hypovolemia associated with exercise dehydration leading to a reduction in brain blood flow may exasperate the displeasure associated with exercising without fiuid leading to greater perceived exertion (18). More simply, it may be that the elevations in Tc, HR, and reduced Pvol in the DEH trial are sensed, and the feedback to the brain results in the greater RPE during exercise at the same relative intensity in a mildly dehydrated state.…”
Section: Discussionsupporting
confidence: 88%
“…Similar results have been reported in other studies investigating the effects of progressive dehydration on RPE (16,20). It is speculated that hypovolemia associated with exercise dehydration leading to a reduction in brain blood flow may exasperate the displeasure associated with exercising without fiuid leading to greater perceived exertion (18). More simply, it may be that the elevations in Tc, HR, and reduced Pvol in the DEH trial are sensed, and the feedback to the brain results in the greater RPE during exercise at the same relative intensity in a mildly dehydrated state.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, RPE became significantly higher in the DEH trial after only 30 min of cycling when subjects had lost <1% body mass. Similar results have been reported in other studies investigating the effects of progressive dehydration on RPE (Ishijima et al, 2009;McGregor, Nicholas, Lakomy, & Williams, 1999). It is speculated that hypovolumia associated with exercise dehydration leading to a reduction in brain blood flow may exacerbate the sense of effort associated with exercising without fluid leading to greater perceived exertion (Maughan, Shirreffs, & Watson, 2007).…”
Section: Effects Of Dehydration On Rpesupporting
confidence: 85%
“…These data support the contention that consuming a volume of fluid equal to sweat losses attenuates cardiovascular drift. Ishijima et al (2009) data also suggest that fluid replacement alone (i.e. with no carbohydrate) may reduce _ VO 2 drift, the effect of which was not measured in the present study.…”
Section: Discussioncontrasting
confidence: 64%
“…In addition, body mass changes do not necessarily reflect a measure of hydration status (Maughan et al 2007). Ishijima et al (2009) showed that during 90 min of cycling at 55% _ VO 2max drinking a hypotonic carbohydrate beverage or mineral water equal to the volume of estimated sweat loss (1.92 ± 0.02 L) reduced cardiovascular and _ VO 2 drift compared with no fluid consumption. These data support the contention that consuming a volume of fluid equal to sweat losses attenuates cardiovascular drift.…”
Section: Discussionmentioning
confidence: 98%